(Invited) Kinetic Parameters in Anion-Exchange Membrane Fuel Cells. (3rd July 2019) - Carlson, Annika Elisabet; Grimler, Henrik; Ekström, Henrik; Lagergren, Carina; Lindbergh, Göran; Wreland Lindström, Rakel
Abstract : Understanding limitations in an operating AEMFC is essential to enhance the technology. Here the electrode processes are studied experimentally as well as by two physics-based models taking the porosity of the electrodes into account. The aim is to use the models to determine kinetic parameters specific for in-situ operation. The models can also be used to explain the experimental behavior. From the impedance model of a symmetric H2 /H2 cell it is shown that the hydrogen oxidation reaction (HOR) proceeds through the Tafel-Volmer reaction pathway, with the hydrogen adsorption as the slower reaction step. Based on the HOR model a steady-state model of an O2 /H2 cell is used to evaluate data from 14 experimental I-V curves, obtained for different gas partial pressures and catalyst loadings, in order to study the effects of the oxygen reduction reaction and overall cell limitations. The results show that the oxygen reduction reaction kinetics limit the cell performance for low current densities. However, at higher currents the uneven current distribution and locally low hydrogen adsorption at the anode increasingly affect the overall performance. Uneven current distribution is also observed at the cathode and likely caused by insufficient effective ionomer conductivity